Pengaruh Pemberdayaan Masyarakat terhadap Kualitas Lingkungan di Sekitar Areal Hutan Tanaman Industri - Ripil Hadi; Rosyani Rosyani; Ermadani Ermadani; Tri Syukria Putra (Universitas Batanghari Jambi, 2023)
The high number of forest and land fires that occur every year can damage the quality of the environment. Serious and continuous efforts are needed to reduce, prevent and control forest and land fires that occur. It is important to do this so that the number of forest and peatland fires caused by humans can be suppressed. One of the efforts that can be done is through community empowerment programs. This study aims to analyze the business and the role and influence of community empowerment on the quality of the environment around the PT Wirakarya Sakti Industrial Plantation Forest Area. This study uses a mixed method approach by combining quantitative research and qualitative research. Based on the results of data analysis, it is known that the environmental quality, including the air quality index, is in the good category (IKU=32,4), the water quality index is good (IKA=0.989) and the soil quality index is in the bad category (IKT=33,5). In addition, it is known that the level of community understanding of forest and peatland knowledge is in the medium category (65.3%), community understanding of forest and land fires is in the medium category (67.1%) and community understanding of community empowerment is in the high (78.2%). The results of the regression analysis prove that the significance value obtained is 0.389>0.05, meaning that community empowerment has no significant effect on environmental quality in the area around industrial plants.